The Main Ways to Ensure the Sustainability of the Financial Position of Contracting Construction Organizations in Uzbekistan - Suyunov A.S; Karjavov Z.K; Suyunova Ya.M, (European Journal of Life Safety and Stability (2660-9630), 2022)
An increase in the cost of facilities during construction against the volume stipulated in the concluded contract (due to inflation) leads to difficulties in normal financing and disruption of the construction period of facilities. The article discusses the need for further improvement of the system of financing and mutual settlements in the construction of Uzbekistan.